Natural Science Learning, Indigenous Science, Donggo Tribe Society, Ethnoscience. - Muthmainnatun, Inna Robbani; Hidayati, Dian (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Utilization of Information and Communication Technology (ICT) in the field of academic administration services in tertiary institutions is a necessity, not just for the dignity or the latest higher education management lifestyle but in its implementation, there are many obstacles that tertiary institutions encounter in implementing ICT in this institutional management process. both technical and non-technical factors. Strengthening governance, accountability and public image of higher education forums will lead to increased performance of higher education institutions and product quality. This policy will be meaningful if it is associated with efforts to provide quality educational institution management services, quality teaching programs, quality educational facilities, and quality education staff as well.